HUBUNGAN HASIL LARI 40 YARD DENGAN KEMAMPUAN LOMPAT JAUH SISWA SISWA KELAS VIII SMPN 2 KECAMATAN SENTAJO RAYA - Farce, Dislagana; Agust., S.Pd, M.Pd, Kristi; ', Drs. Saripin., M.Kes AIFO (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The problem in this research is the result of the long jump which is owned by the students of class VIII SMPN 2 Sentajo Raya district. This problem is suspected because of the 40 yard dash speed of the students. The purpose of this study was to prove whether there is a corelation 40 yard dash results with the long jump ability on class VIII students of SMPN 2 Sentajo Raya district. The method used is the correlation method-method used to determine the degree of correlation between the different variables. The population in this study were students of class VIII SMPN 2 Sentajo Raya district, which amounted to 18 people. The sample selection using total sampling technique thus the sample in this study were students of class VIII SMPN 2 Sentajo Raya district namely 18 people. Analysis of data using correlation and regression analysis. Before testing the hypothesis to test hypotheses and analysis requirements for linearity test regression line by F test using a significance level of 5%. Obtained Fcount = 0.83> F table = 4:41, and the regression equation is Y = 16.75 + 0.83x. Furthermore, to test the truth of the correlation between variables X and Y then tested the significance of using the formula t test of significance. The calculation of the results t = 2.79, while table = 1,746. Thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) that